O estranhamento na experiência da enfermidade - Anhanha, Brenda Rossi (2023)
The phenomenology of illness differs from the biostatistical theory of Christopher Boorse and the holistic theory of Lennart Nordenfelt: 1) The biostatistical theory takes into account the biological aspects of disease, in other words, it considers the nature of the body as essential to health, and assigns to biology the role of determining if a body - a biological organism - is healthy or not; 2) The holistic theory, in turn, does not focus on the biological organism, but on the individual that acts in a social world: the well-being of people does not depend solely on their biological status, but also on their choices; 3) On the other hand, the phenomenology of illness falls within the group of the theories of health and has as its objective characterizing health and illness. And although it does not rely mainly on biology, the phenomenological account understands embodiment as a key concept, especially in the case of illness. Therefore, the phenomenology of illness starts off from the first person perspective and aims to characterize the structural components of the experience of illness by framing it as a disturbance of the lived body. In some interpretations, the concept of uncanniness (Unheimlichkeit) of Martin Heidegger is incorporated into the analysis of the experience of illness, as is the case of Fredrik Svenaeus and Andrew Warsop, among others. Katherine Withy, in turn, characterized the problem of uncanniness, although she does not address illness. In this direction, the present dissertation has the goal of analyzing the aspects of illness, as well as the link between the experience of illness and the concept of uncanniness in the work of Martin Heidegger. The dissertation is divided in four articles: 1) Phenomenology of Illness: A Brief Reconstruction; 2) The Importance of Existential Feelings to the Experience of Illness; 3) The Experience of the Body in Illness; 4) The Uncanniness According to Katherine Withy and its Link to the Experience of Illness.